Computational modelling of Cold-formed steel lap joints with screw fasteners. (October 2021) - Quan, Guan; Ye, Jun; Li, Wenchao
Abstract: The self-tapping screw connectors are widely used in Cold-formed Steel (CFS) construction due to their rapid fastening with automatic power driving and ease of installation via a self-drilling process. However, there is a lack of a robust numerical method for the modelling of behaviours of screw fasteners bearing against steel sheets, where the connections can undergo different failure modes including fracture, bearing, tilting, pull-out and shear failure, particularly for CFS thin plates. A nonlinear explicit dynamic finite element (FE) model is developed in this paper to address this issue by validating the modelled load-deformation relationships and failure modes with available tests in literature. The proposed numerical model is improved in two aspects comparing to available research: firstly, a ductile fracture criterion was proposed that could address the fracture of ply metals subjected to complex stress state with less trial-and-error process. Secondly, the threads in the screw fasteners and ply sheets were carefully modelled where the inter-locking capacity between the screws and steel sheets were better taken into account, eliminating the need for an artificial friction factor. The FE modelled results were compared against the test results and showed good agreement in terms of connection strength and failure modes, including fracture, bearing, tilting, pull-out and shear failure. Finally, parametric studies were carried out to investigate the influence of steel sheet thickness and the screw outer diameter on the force–displacement relationships of the steel lap joints.